Physicochemical Characterization and Antioxidant and Hypolipidaemic Activities of a Polysaccharide From the Fruit of Kadsura coccinea (Lem.) A. C. Smith - Long, Hairong; Xia, Xianghua; Liao, Suqi; Wu, Tao; Wang, Lijun; Chen, Qianping; Wei, Shugen; Gu, Xiaoyu; Zhu, Zhenjun (Frontiers in Nutrition, 2022)
Kadsura coccinea fruit, a novel fruit resource, has attracted wide interest, but the physicochemical characteristics and biological activities of its polysaccharides remain unclear. This study investigated the physicochemical properties of a polysaccharide extracted from K. coccinea fruit (KCFP) and evaluated its antioxidant and hypolipidaemic activities in vitro and in vivo. KCFP is an amorphous, thermally stable pectin heteropolysaccharide with an average molecular weight of 204.6 kDa that is mainly composed of mannose, rhamnose, glucose, galactose, xylose, arabinose, galacturonic acid (molar percentage >70%) and glucuronic acid. 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) free radical scavenging assays and an iron reducing antioxidant power assay showed that KCFP has strong antioxidant capacity, while the bile acid binding assay showed that KCFP has hypolipidaemic potential in vitro. The antioxidant and hypolipidaemic activities of KCFP were further evaluated in high-fat diet-induced hyperlipidaemic mice. KCFP significantly increased the activities of superoxide dismutase, glutathione peroxidase and catalase, decreased the malondialdehyde content, significantly reduced the total cholesterol (TC), triglyceride (TG) and low-density lipoprotein cholesterol (LDL-C) levels, and increased the amount of high-density lipoprotein cholesterol (HDL-C). These findings suggest that KCFP could be used as a functional food to remedy oxidative damage and hyperlipidaemia.